Sport and leisure: The importance of professional, technical and scientific management (Research, Society and Development, 2024)
This study adopts the bibliographic review method with the aim of identifying in a defragmented way how the systematization of public sports and leisure policies occurs in Brazilian states and municipalities, so that it is possible to elucidate effective means capable of expanding access to quality policies that go beyond the mere organization of sporting events, and that, in addition, it is possible to encourage the qualification and professionalization of managers in each department. To carry out the review, works published between 2012 and 2022, available on the Scielo and Google Scholar platforms, were selected and used. Choosing this period allows a comprehensive overview of the latest policies and current trends in the sport and leisure sector. By compiling and examining these sources, the study seeks to provide a detailed and critical overview of the current situation, highlighting both the advances and challenges faced. Therefore, the final objective is to present concrete recommendations for improving public policies, ensuring that they are more inclusive, continuous and effective. It is also hoped that with these improvements, society can benefit from policies that promote general well-being, encourage the regular and effective practice of sports and leisure activities, and contribute to social and community development in a sustainable and equitable manner.